Effects of land use/land cover and climate changes on terrestrial net primary productivity in the Yangtze River Basin, China, from 2001 to 2010. Issue 6 (13th June 2014) - Zhang, Yulong; Song, Conghe; Zhang, Kerong; Cheng, Xiaoli; Band, Lawrence E.; Zhang, Quanfa
Abstract Land use/land cover change (LULCC) and climate change are among the primary driving forces for terrestrial ecosystem productivity, but their impacts are confounded. The objective of this paper is to decouple the effects of LULCC and climate change on terrestrial net primary productivity (NPP) in China's Yangtze River Basin (YRB) during 2001–2010 using a light use efficiency model through different scenario designs. During the study period, the YRB witnessed tremendous LULCC and climate changes. A prominent LULCC was the conversion of shrub land to forests as a result of a series of forest restoration and protection programs implemented in the basin. At the same time, notable warming and drying trends were observed based on ground and satellite measurements. Prescribed model simulations indicated that LULCC alone had a significantly positive effect on total NPP (up to 6.1 Tg C yr−1, p < 0.01) mainly due to reforestation and forest protection, while climate change alone showed an overall negative effect in the basin (as much as −2.7 Tg C yr−1, p = 0.11). The ensemble effect of LULCC and climate change on total NPP is approximately 3.9 Tg C yr−1 (p = 0.26) during 2001–2010. Our study provides an improved understanding of the effects of LULCC and climate change on terrestrial ecosystem productivity in the YRB. We found that reforestation and forest protection could significantly enhance terrestrial ecosystem productivity, a strategy that could mitigate global warming. It also suggests that NPP models with static land use/land cover could lead to increasingly large errors with time.